“Heart Oddity”: Intrinsically Reduced Excitability in the Right Ventricle Requires Compensation by Regionally Specific Stress Kinase Function - Zaitsev, Alexey V.; Warren, Mark (Frontiers in Physiology, 2020)
The traditional view of ventricular excitation and conduction is an all-or-nothing response mediated by a regenerative activation of the inward sodium channel, which gives rise to an essentially constant conduction velocity (CV). However, whereas there is no obvious biological need to tune-up ventricular conduction, the principal molecular components determining CV, such as sodium channels, inward-rectifier potassium channels, and gap junctional channels, are known targets of the “stress” protein kinases PKA and calcium/calmodulin dependent protein kinase II (CaMKII), and are thus regulatable by signal pathways converging on these kinases. In this mini-review we will expose deficiencies and controversies in our current understanding of how ventricular conduction is regulated by stress kinases, with a special focus on the chamber-specific dimension in this regulation. In particular, we will highlight an odd property of cardiac physiology: uniform CV in ventricles requires co-existence of mutually opposing gradients in cardiac excitability and stress kinase function. While the biological advantage of this peculiar feature remains obscure, it is important to recognize the clinical implications of this phenomenon pertinent to inherited or acquired conduction diseases and therapeutic interventions modulating activity of PKA or CaMKII.